Did Crime Rise or Fall During the Reagan Presidency? The Effects of an "Aging" U.S. Population on the Nation's Crime Rate - Steffensmeier, Darrell J. (Journal of research in crime and delinquency, 1991)
In this article we apply age-standardization methods to the Uniform Crime Reports (UCR) and the National Crime Survey (NCS) to determine whether the drop in the nation's Crime Rate from 1980 to 1988 (the Reagan period) is due to changes in the age structure of the population. Our major findings are that the age-adjusted Crime Index increases 7% in the UCR but declines 7% in the NCS. This contrasts to a 4% drop in the crude UCR index rate and 17% drop in the crude NCS index rate. Overall, the age adjustment explains the entire drop (100% +) in the reported or crude index rate in the UCR and about 60% of the drop in the NCS. When examined over a longer period - 1976 to 1988 - the UCR shows rates that, fluctuate but tend to rise overall, whereas the NCS shows fairly stable or slightly declining rates. The crime-fighting stance of the Reagan years which emphasized stricter enforcement and greater sanction threat (aimed mainly at street crime and drug trafficking) dramatically increased rates of imprisonment. But no discernible reduction in crime rates occurred, suggesting that no law enforcement strategy can be confidently recommended as a remedy to the nation's crime problem